Relationship between Covid-19 Pandemic and Changes in Sleep Pattern in Children Diagnosed with Autism Spectrum Disorder - Andintia Aisyah Santoso; Adantio Rashid Santoso; R.A. Deta Hanifah; Rini Sekartini (eJournal Kedokteran Indonesia, 2022)
Studies showed that COVID-19 lockdown has caused changes in sleep-wake rhythms and sleep disturbances in a large percentage of the population, related to limitation of activities. Specific populations such as ASD children were predicted to experience greater difficulties due to disruption of strictly bound daily routine. This review aimed to systematically investigate whether children diagnosed with ASD during the COVID-19 pandemic experienced any changes in their sleep patterns. We performed a journal search from PubMed, Cochrane Library, EBSCO, Proquest, and Scopus databases starting on January 1st 2020 until August 12th 2021. The searches were limited to study with ASD children (0-18 years) population samples without other neurodevelopmental disorders. Of 12 articles screened, 4 studies were included. Our included studies found that in ASD children there is no significant difference (p>0.05) in sleep duration changes between pre-pandemic and during the pandemic period while several sleep quality problems such as longer sleep latency, anxiety at bedtime, sleep terrors, daytime sleepiness, and night wakings showed a significant increase (p<0.05). COVID-19 pandemic is thought to disrupt children with ASD sleep patterns and multifactorial aspects need to be evaluated further. Keywords: autism spectrum disorder, children, COVID-19, pandemic, sleep patterns.   Hubungan Pandemi COVID-19 dengan Perubahan Pola Tidur pada Anak Terdiagnosis Autism Spectrum Disorder Abstrak Beberapa studi menunjukkan bahwa lockdown pada pandemi COVID-19 telah menyebabkan perubahan ritme tidur-bangun dan terjadinya gangguan tidur pada sebagian besar populasi, berkaitan dengan terbatasnya aktivitas. Populasi spesifik seperti anak dengan autism spectrum disorder (ASD) diperkirakan mengalami tantangan yang lebih besar karena adanya perubahan pada rutinitas harian yang semula sangat teratur. Tinjauan ini dibuat untuk menelusuri apakah anak ASD mengalami perubahan pola tidur selama pandemi COVID-19. Kami melakukan pencarian jurnal melalui basis data PubMed, Cochrane Library, EBSCO, Proquest, dan Scopus yang dipublikasikan mulai 1 Januari 2020 hingga 12 Agustus 2021. Pencarian terbatas pada populasi sampel yakni anak dengan ASD (0-18 tahun) tanpa adanya gangguan perkembangan saraf lainnya. Dari 12 artikel terpilih, empat di antaranya memenuhi kriteria untuk dimasukkan ke dalam tinjauan ini. Studi-studi yang kami temukan menunjukkan bahwa tidak ada perubahan signifikan (p>0,05) pada pola tidur anak ASD sebelum pandemi dibandingkan selama pandemi sementara beberapa masalah kualitas tidur seperti latensi tidur yang lebih lama, kecemasan pada jam tidur, sleep terrors, rasa mengantuk pada pagi hari, dan terbangun di malam hari menunjukkan peningkatan yang signifikan (p<0,05). Pandemi COVID-19 dipikirkan dapat mengganggu pola tidur anak dengan ASD dan berbagai aspek multifaktorial perlu dipelajari lebih lanjut. Kata kunci: anak, autism spectrum dIsorder, COVID-19, pandemi, pola tidur.